Strategic Human Resource Management in Health Sector in Kenya (Global Journal of Management and Business Research, 2014)
The scope of the research study includes an overview of human resource management at the national, county and institutional levels. The research methodology consists of a literature review of journals on human resource management, annual reports from health facilities, and government documents. This research consists of an empirical and conceptual analysis on the relationship between human resource management and performance. The research study examines theories on human resource management practices in an attempt to develop an understanding of theoretical and rational ways in which human resource management practices affect the performance of the health facilities. Aligning people management with the business strategy and integrating high performance work systems into the strategic management process is crucial for improving performance of health facilities and delivery of quality services. This paper provides a framework for guiding development of Human Resourcepolicies and practices within the health sector in Kenya.
Keywords: human resource management; financial performance; competitive advantage; turnover